2005
DOI: 10.1089/end.2005.19.1221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Holding Strength of Suture Anchors for Hepatic and Renal Parenchyma

Abstract: Results: The force required to dislodge the Lapra-Ty clip from bare suture for both 0 and 1 Vicryl (7.0 N) was approximately fourfold the force required to dislodge the Endoclips or the 5-mm or 10-mm Hem-o-lok clips (p Ͻ 0.01). When clips were applied to suture running through renal or liver parenchyma, the novel Suture-clip required the greatest tension to dislodge (P Ͻ 0.01), followed by the Horizon and Lapra-Ty clips. There were no statistically significant differences in the tension required to dislodge a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In addition, there have been 2 similar studies evaluating specifically suture anchors for renal and hepatic parenchyma. In the first study, Ames et al 11 laid the grounds for lower ischemia time during laparoscopic partial nephrectomy using anchored sutures instead of the classic intracorporeal suturing. Furthermore, Tarin et al 12 concluded that using Hem-o-lok suture anchors results in a more secure and cost-effective closure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there have been 2 similar studies evaluating specifically suture anchors for renal and hepatic parenchyma. In the first study, Ames et al 11 laid the grounds for lower ischemia time during laparoscopic partial nephrectomy using anchored sutures instead of the classic intracorporeal suturing. Furthermore, Tarin et al 12 concluded that using Hem-o-lok suture anchors results in a more secure and cost-effective closure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Of the various methods used to ensure hemostasis, Hem-o-lok clip application is safe and reliable for vascular control during laparoscopic procedures. 3 During RALRP, Hem-o-lok clips are used posterolaterally for control of the vascular pedicles and posteriorly for ligation of the vas deferens. The mechanisms proposed for clip migration are as follows: the clips placed over the bladder wall for hemostasis possibly became incorporated into the vesicourethral anastomosis, or perhaps the clips fell into the urinary bladder during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Safety of the knotless suturing depends on the tensile strength required to dislodge sutures. In one study using fresh pig kidney and liver, five clips were assessed: the Lapra-Ty, Endoclip II, small Horizon Ligating Clips, Hem-o-lok Medium Polymer Clips, and a novel Sutureclip [44]. The Suture-clip, Lapra-Ty, and Horizon clips required significantly greater tension to dislodge than the Hem-o-lok and Endoclip clips; addition of a pledget did not improve tension resistance.…”
Section: Knotless Suturingmentioning
confidence: 99%